Essential-oil pesticidal odorscapes: An exploratory multi-endpoint framework for profiling plant volatiles against walnut-associated stored-product beetles - Gabriel Omar Denett; Maria Rosa Rodriguez; Virginia L. Usseglio; Daniela Milagros Bracamonte; Tamara Elizabeth López; Jose Francisco Aranda Cano; María Paula Zunino; Jorge Omar Werdin Gonzalez; Diego Alejandro Sampietro; Nieves Carolina Comelli (Journal of Stored Products Research, 2027)

Fracture energy estimation in mortar: a dual-method approach integrating three-point bending experiments and numerical simulation - Omar Rodriguez-Villarreal; Firas Al Mahmoud; Moises Hinojosa-Rivera; Christian La Borderie; Gilles Pijaudier-Cabot; Hui Wang (European Journal of Environmental and Civil Engineering, 2026)

Hybrid Sparrow Search Algorithm Support Vector Machine Regression Bidirectional Long-Short Term Memory (SSA-SVR-BiLSTM) model with Lagrange-based weighting for PM$$_{2.5}$$ prediction and stratified evaluation - Maria Fernanda Camargo; Sergio Diaz; Ricardo Elias Celis Parra; Vladimir Ramírez Tarazona; Astrith Eugenia Rincón Sánchez; V. Rodriguez-Rueda; Omar F. Rojas-Moreno; Alejandra Baena (Environmental and Ecological Statistics, 2026)
Air pollution is a major environmental risk to public health, strongly associated with cardiovascular and respiratory diseases. According to the World Health Organization, at least 99% of the global population lives in areas that do not meet its air-quality guidelines. PM $$_{2.5}$$ 2.5 variability reflects the interaction between local emission sources and meteorological processes that regulate near-surface dispersion and accumulation, producing nonlinear temporal patterns that motivate hybrid modeling approaches. We propose an SSA-SVR-BiLSTM framework for short-term PM $$_{2.5}$$ 2.5 forecasting that combines SSA-optimized SVR and BiLSTM models within a constrained linear ensemble with weights estimated exclusively on the validation partition using Lagrange multipliers. The model is evaluated on 10 months of high-frequency (5-min) air-quality and meteorological data collected at a traffic-influenced monitoring site in Duitama, Colombia. On the held-out test set, the hybrid achieved $$R^2 = 0.9585$$ R 2 = 0.9585 and MAPE $$= 7.62%$$ = 7.62 % , outperforming five of six SSA-optimized baselines; the difference relative to the best individual model (SSA-SVR was statistically significant but practically negligible ( $$p = 0.0105$$ p = 0.0105 , $$Δ R^2 = 0.0002$$ Δ R 2 = 0.0002 ), and the value of the hybrid lies primarily in its improved consistency across low and medium concentration regimes rather than in a large global accuracy gain. Stratified evaluation across concentration regimes and normative thresholds (WHO, EPA) revealed systematic underestimation at extreme pollution episodes, a structural limitation shared by all evaluated models. A feature occlusion analysis identified PM $$_5$$ 5 and PM $$_{10}$$ 10 as the dominant exogenous predictors (53.6 and 21.7%), with meteorological variables contributing an additional $${\sim }20%$$ ∼ 20 % of the total relevance.

Genetic diversity among three Mexican local goat populations assessed by microsatellite DNA markers - Irlanda J. Siliceo-Cantero; Glafiro Torres-Hernández; Ricardo Lobato-Ortíz; Samuel Vargas-López; Omar Hernández-Mendo; Javier Suárez-Espinoza; Martha Hernández-Rodriguez; Jorge A. Maldonado-Jáquez (Tropical Animal Health and Production, 2026)

IoT-enabled air quality prediction using ensemble machine learning: a case study in San Salvador, El Salvador - Josue Ramirez-Ramirez; Daniel Amaya-Cruz; Griselda Zepeda-Navarro; Bayron Carpio-Villaran; Miguel Alfaro-Vides; Yakdiel Rodriguez-Gallo; Omar Otoniel Flores-Cortez; Carlos Osmín Pocasangre Jiménez; Werner David Meléndez (Air Quality, Atmosphere & Health, 2026)

Functional connectivity alterations in spinocerebellar ataxia type 10: insights from gray matter atrophy - Gustavo Padron-Rivera; Gabriel Ramirez‐Garcia; Amanda Chirino‐Perez; Angel Omar Romero-Molina; Adriana Ochoa-Morales; María Guadalupe Garcia-Gomar; Miguel Angel Ramirez‐Garcia; Omar Rodriguez-Mendoza; Diana Laura Torres-Vences; Birgitt Schüle; Erick Humberto Pasaye-Alcaraz; Carlos Roberto Hernandez-Castillo; et al. (Brain Imaging and Behavior, 2026)
Spinocerebellar ataxia type 10 (SCA10) is a rare, inherited neurological disease caused by an expansion of the non-coding ATTCT pentanucleotide repeat in the ATAXIN 10 gene. It is characterized by cerebellar ataxia and epilepsy. Previous research has demonstrated extensive white and gray matter degeneration, particularly in the cerebellum. However, the impact of the SCA10 mutation on functional connectivity (FC) remains unexplored. This study aimed to characterize intrinsic FC changes in SCA10 patients and their relationship to clinical manifestations. Structural and resting-state Magnetic Resonance Imaging (MRI) were obtained from 26 SCA10 patients and 26 control subjects. Voxel-based morphometry (VBM) and seed-ROI and Independent Components Analysis (ICA) were performed to identify cerebral atrophy and FC changes respectively. Additionally, correlation analyses were conducted between FC changes and scores from the Scale for the Assessment and Rating of Ataxia (SARA) and the Montreal Cognitive Assessment (MoCA). In SCA10 patients, VBM analysis revealed extensive gray matter loss in motor cortices and the cerebellum. FC analysis identified significant FC changes originating from seed-ROIs in the right cerebellar VI and left precentral gyrus. Furthermore, group comparison using ICA components showed that SCA10 patients exhibited higher FC in the sensorimotor and cerebellar functional networks. Moreover, the average Blood Oxygen Level Dependent (BOLD) signal within the cerebellar network negatively correlated with MoCA scores. In summary, SCA10 patients exhibited enhanced FC in brain regions that displayed gray matter atrophy, underscoring the impact of SCA10 degeneration on resting state networks and induction of potential maladaptive FC compensatory mechanisms.

Impact of fluoride on antioxidant activity and mitochondrial homeostasis in fetal rat kidney - Sabino Hazael Avila-Rojas; Esaú Montañez-Rodriguez; Ana Karen Pantaleón-Gómez; Iliana Angélica Tostado-Fernández; José Pedraza-Chaverri; Casimiro Gerarduzzi; Omar Noel Medina-Campos; Brenda Marquina-Castillo; Juan Carlos León-Contreras; Rogelio Hernández-Pando; Olivier Christophe Barbier (Toxicology, 2026)

Population dynamics and somatic production of burrowing shrimp assemblage in a Mexican estuary under ENSO-driven temperature fluctuations - Ignacio Caceres; Omar Hernando Avila-Poveda; Sandra Rodriguez-Huezo; Fabian Alejandro Rodriguez-Zaragoza; Manuel Ayon-Parente (Regional Studies in Marine Science, 2026)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Seasonal and Habitat-related Variations in the Cuticular Chemical Profile of Atta sexdens (Hymenoptera: Formicidae) Foraging Workers - Jean Carlos Dos Santos Lima; Omar Bailez; Jonathan Rodriguez Guerrero; Anália Arêdes; Maria Cristina Canela; Ana Maria Viana-Bailez (Neotropical Entomology, 2025)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Experimental and microstructural study of concrete reinforced with maguey fiber: Peruvian case - Bakner Yanverly Paisig Saucedo; Sócrates Pedro Muñoz Pérez; Juan Martína García Chumacero; Elver Sánchez Diaz; Luigi Italo Villena Zapata; Edwin Adolfo Diaz Ortiz; Ernesto Dante Rodriguez Laffite; Omar Coronado Zuloeta; Carlos Eduardo Ramos Brast (Innovative Infrastructure Solutions, 2024)

Exploring the nexus of urban form, transport, environment and health in large-scale urban studies: A state-of-the-art scoping review - Georgia M.C. Dyer; Sasha Khomenko; Deepti Adlakha; Susan Anenberg; Martin Behnisch; Geoff Boeing; Manuel Esperon-Rodriguez; Antonio Gasparrini; Haneen Khreis; Michelle C. Kondo; Pierre Masselot; Robert I. McDonald; et al. (Environmental Research, 2024)

Corrigendum to: “From waste to food and bioinsecticides: An innovative system integrating Tenebrio molitor bioconversion and pyrolysis bio-oil production” [Chemosphere 340 (2023)139847] - Rodrigo Iñaki Urrutia; Emiliano Nicolas Jesser; Victoria Soledad Gutierrez; Silvana Rodriguez; Fernanda Gumilar; Ana Paula Murray; Maria Alicia Volpe; Jorge Omar Werdin-González (Chemosphere, 2023)

From waste to food and bioinsecticides: An innovative system integrating Tenebrio molitor bioconversion and pyrolysis bio-oil production - Rodrigo Iñaki Urrutia; Emiliano Nicolas Jesser; Victoria Soledad Gutierrez; Silvana Rodriguez; Fernanda Gumilar; Ana Paula Murray; Maria Alicia Volpe; Jorge Omar Werdin-González (Chemosphere, 2023)

Upper Limb Recovery in Cervical Spinal Cord Injury After a Brain-Computer Interface Controlled Functional Electrical Stimulation Intervention - Jessica Cantillo-Negrete; Ruben I. Carino-Escobar; Ismael Leyva-Martinez; Aida Barrera-Ortiz; Marlene A. Rodriguez-Barragan; Omar Mendoza-Montoya; Javier M. Antelis (Journal of Medical and Biological Engineering, 2023)

Influence of rice husk ash (RHA) with gypsum and ichu fibers in the processing of geopolymers - Sócrates Pedro Muñoz Pérez; Samuel Charca Mamani; Luigui Italo Villena Zapata; Jorge Luis Leiva Piedra; Simon Gonzales Ayasta; Ernesto Dante Rodriguez Lafitte; Fidel Gregorio Aparicio Roque; Omar Coronado Zuloeta (Innovative Infrastructure Solutions, 2023)

Abundance and distribution of potentially toxic phytoplankton in aquaculture sites along the Peruvian coast - Tomasa Cuellar-Martinez; Aurora del Rocío Huanca Ochoa; Sonia Sánchez; Arturo Aguirre-Velarde; Elmer Omar Martínez Ocas; Angélica María Rodriguez Velasquez; Rosa Isabel Saavedra Querevalú; François Colas; Jorge Tam; Dimitri Gutiérrez (Journal of Marine Systems, 2023)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Early warning system for rainfall-triggered landslides based on real-time probabilistic hazard assessment - Oscar Correa; Francisco García; Gabriel Bernal; Omar Darío Cardona; Carlos Rodriguez (Natural Hazards, 2020)

Reproductive traits and relative gonad expenditure of the sexes of the free spawning Chiton articulatus (Mollusca: Polyplacophora) - Quetzalli Yasu Abadia-Chanona; Omar Hernando Avila-Poveda; Marcial Arellano-Martinez; Bertha Patricia Ceballos-Vazquez; Francisco Benitez-Villalobos; Geoff A. Parker; Guillermo Rodriguez-Dominguez; Sergio Garcia-Ibañez (Invertebrate Reproduction & Development, 2018)